Cover Image: Volume 25 Number 3, March 2022. (24th February 2022) - Tobias, Joseph A.; Sheard, Catherine; Pigot, Alex L.; Devenish, Adam J. M.; Yang, Jingyi; Sayol, Ferran; Neate‐Clegg, Montague H. C.; Alioravainen, Nico; Weeks, Thomas L.; Barber, Robert A.; Walkden, Patrick A.; MacGregor, Hannah E. A.; et al.
Abstract : The cover image is based on the Letter AVONET: morphological, ecological and geographical data for all birds by Tobias et al., https://doi.org/10.1111/ele.13898 . The sword‐billed hummingbird ( Ensifera ensifera ) is exquisitely adapted to its trophic niche as an aerial pollinator of flowerings plants (angiosperms) in the high Andes. A new global dataset of detailed ecomorphological traits for all birds offers a resource with numerous potential uses in ecology, evolution, and conservation biology. Image Credit: Cover Image © Oliver Krüger. Reproduced with permission.